229k views
0 votes
If f(x)=1/9x-2, what is f^–1(x)?

A.) f^–1(x) = 9x + 18
B.) f^-1(x)=1/9x+2
C.) f^–1(x) = 9x + 2
D.) f^-1(x)=-2x+1/9

If f(x)=1/9x-2, what is f^–1(x)? A.) f^–1(x) = 9x + 18 B.) f^-1(x)=1/9x+2 C.) f^–1(x-example-1
User Jparaya
by
5.5k points

2 Answers

3 votes

f(x)=19x+2→ Switch the f(x) with a y


y=19x+2→ Switch the places of the x and the y variables


x=19y+2→ Solve for y


x−2=19y


y=9x−18


The inverse is f−1(x)=9x−18

User Hypers
by
6.1k points
3 votes

Answer:

Option A is correct


f^(-1)(x) = 9x+18

Explanation:

Given the function:


f(x) =(1)/(9)x-2

Let y = f(x)

then;


y=(1)/(9)x-2

Replace x and y values we have;


x=(1)/(9)y-2

Add 2 to both sides we have


x+2=(1)/(9)y

Multiply both sides by 9, to solve for y


9(x+2) = y

or

y = 9(x+2)

replace
y = f^(-1) (x) then;


f^(-1)(x) = 9(x+2)


f^(-1)(x) = 9x+18

therefore, the inverse of f(x) is,
f^(-1)(x) = 9x+18

User Dharmishtha
by
5.7k points